PENGELOLAAN SUPERVISI KLINIS BERBASIS KUALITAS (STUDI SITUS SDN 1 TAMBAHREJO KECAMATAN PAGERUYUNG KABUPATEN KENDAL) - Purwanto , Widodo Dwi (2011)
The research focus is "How is the characteristic of clinical supervision based quality in SDN 1 Tambahrejo, Pageruyung, Kendal?". The purposes of this research are to (1) describe the implementation of organizational characteristics of clinical supervision based on the quality in SDN 1 Tambahrejo, Pageruyung, Kendal. (2) To describe the characteristics of labor relations between supervisor and teacher in SDN 1 Tambahrejo, Pageruyung, Kendal. (3) Describe the characteristics of a work supervisor in SDN 1 Tambahrejo, Pageruyung, Kendal. The type of research used qualitative research and ethnographic design. This research was conducted in SDN 1 Tambahrejo, Pageruyung, Kendal. The main subjects are the leader of t institutions, educators and representatives of leader in the institution in SDN 1 Tambahrejo, Pageruyung, Kendal. Methods of data collection used interviews, observation, and documentation. The data analysis starts from (1) Data Collection, (2) data reduction, (3) display data, and (4) conclusion. Test the validity of the data using the credibility, transferability, conformability and dependability. The results of this research are (a). The implementation of organizational characteristics of clinical supervision based on the quality is including school principals, teachers and supervisors. School principals guide teachers; conduct good preparation by school principals and teachers. Human resources of organizational supervision are highly qualified providers. Organizations such as the publication time strategy implementation supervision, by random selection of teachers, provide guidance to teachers, and conduct direct and indirect supervision. Schools made coordination with LPMP to upgrade the skills of teachers. (2) The characteristics of labor relations between supervisor and teacher includes armed with the arrival of supervisors who come unannounced, coordinating with teachers, doing a harmonious relationship, conduct discussions, avoiding selfishness, to communicate effectively and provide solutions to the teacher who get less value or are having problems. (3) the characteristics of a work supervisor is not a threat to the teachers, have the optimal performance is influenced by less capability of teachers, principals, professional supervision with the use of two strategies in the classroom and outside the classroom, and performance in accordance with the purpose supervisor who want to achieve is to improve the commitment of teachers and teachers' level of abstraction.